Robust Hydrogen Production via Pickering Interfacial Catalytic Photoreforming of n-Octanol-Water Biphasic System - Wang, Chao; Zhong, Weilin; Peng, Suqing; Zhang, Jingtao; Shu, Riyang; Tian, Zhipeng; Song, Qingbin; Chen, Ying (Frontiers in Chemistry, 2021)
Pickering emulsion offers a promising platform for conducting interfacial reactions between immiscible reagents; it is particularly suitable for hydrogen production by photoreforming of nonwater soluble biomass liquid and water. Herein, Pt-promoted (001)-facet-dominated anatase TiO2 nanosheets were synthesized by a hydrothermal route associated with microfluidic technology for high activity and metal dispersion, and selective surface modification was carried out for preparing Janus particles. Photoreforming hydrogen production through n-octanol and water that formed O/W microemulsion with an average diameter of 540 µm was achieved to obtain amphiphilic catalyst. The as-prepared 2D Janus-type catalysts exhibited remarkably stable emulsification performance as well as photocatalytic activity. This finding indicates that triethoxyfluorosilane had negligible impact on the catalytic performance, yet provided a remarkable benefit to large specific surface area at microemulsion interface, thereby enhancing the H2 yield up to 2003.47 µmol/g. The cyclic experiments indicate that the decrease in cyclic performance was more likely to be caused by the coalescence of the microemulsion rather than the decrease in catalytic activity, and the microemulsion could be easily recovered by simply hand shaking to more than 96% of the initial performance.